The Interventionist Role of the Upper Nobility in Castilian Towns during the Late Middle Ages: the Marshals of Castile in Soria (SP) (Edad Media. Revista de Historia, 2017)
A contribution to the study of the role that members of the Castilian high nobility played in politics and society in the royal towns by the end of the 15th and the beginning of the 16th centuries. The paper analyzes the case of the town of Soria, where only a few nobles of relatively high rank lived at this time, and proves that the lords of Ciria and Borobia, members of a minor branch of the Arellano family, tried to become members of the ruling elite of Soria, yet had to face strong resistance. Only after the revolt of the “Comunidades” broke out, a member of this family, Carlos de Arellano, succeeded in playing a more active role in the local politics of Soria. After the revolt was crushed, he tried to continue playing this role, but failed in the medium term.
Keywords: 15th century; 16th century; crown of Castile; Soria; upper nobility; towns